Production and quality of ornamental peppers cultivated under colored shade nets - Cruz, Renata Ranielly Pedroza; Pereira, Ariana Mota; Santos, Erli Pinto dos; Silva, Toshik Iarley da; Ferreira, Felipe Douglas; Ribeiro, Wellington Souto; Peternelli, Luiz Alexandre; Grossi, José Antonio Saraiva (Comunicata Scientiae, 2024)
The cultivation of ornamental peppers in places with high temperature and incidence of solar radiation limits the production and quality of plants and fruits. The colored shade nets were introduced and adopted, because they reduce the temperature and intensity of solar radiation, as well as, low cost and simple to handle. The aimed was to evaluate the production and quality of C. chinense and C. frutescens cultivated under colored shade nets. The experiment was developed in the Floriculture Sector of the Agronomy Department of the Universidade Federal de Viçosa, Viçosa, Minas Gerais, Brazil from February to August 2021 in entirely randomized design. C. chinense and C. frutescens were cultivated under red, pearl and aluminet nets with 35% shading and without net. At 150 days, production variables were quantified. The red net reduced the maximum temperature by at 4.1ºC and the pearl and aluminet nets reduced the minimum temperature by 3ºC. The maximum and minimum relative humidity was increased by 2.6 and 8.5%, respectively, by the red net. The pearl net obtained the lowest percentage of solar radiation incidence. Plant height was greater in the red and pearl nets, and C. frutescens. The diameter and stem fresh matter did not differ statistically between treatments. Root length was greater in the red and aluminet nets. The longitudinal and transverse canopy ratio was higher in C. chinense cultivated under the aluminet net. The number of leaves and leaves fresh matter was higher in pearl and aluminet net, and in C. frutescens, but leaves dry matter was higher in C. chinense. The number of flower buds and flowers, and flower buds dry matter was higher in C. chinense. The root fresh matter and dry matter was greater in C. chinese. The use of colored shade nets during the cultivation period effectively reduced temperature and light intensity. The aluminet net in association with C. chinense are recommended considering the compactness of height, pot coverage, greater number, shape and arrangement of fruits.